Understanding the dignity experience and exploring the impact of dignity therapy and guided imagery on patients with advanced disease - a South African perspective - Balbadhur, Raksha (Department of Public Health and Family Medicine, 2017)
Objectives: This study was conducted to understand the dignity experience of patients with advanced disease from diverse socio-economic and cultural backgrounds in a South African context. In addition, the psychotherapeutic interventions, Dignity Therapy and Guided Imagery (focused on intrinsic dignity), were implemented to enhance the dignity experience of these patients and its impact explored. Method: This was a qualitative study where a semi-structured interview guide was used in the exploration of the understanding of the dignity experience of patients with advanced diseases, receiving home care from two hospices in the North of Durban, KwaZulu-Natal. Interviews were audiotaped and transcribed verbatim. Data was analysed using thematic analysis. Dignity Therapy and Guided Imagery were subsequently implemented with these patients. Dignity therapy is an appreciative enquiry into the lives of patients to allow them to discuss aspects of their life that matter most, and the legacy and words of advice they would want most remembered. The sessions are audiotaped, transcribed and edited to produce a legacy document that can be given to their family or loved ones, if they so wish. Guided Imagery was implemented to affirm a practical experience of patients' intrinsic dignity and worth as beings. A post intervention patient feedback questionnaire, which involved a quantitative and qualitative component, was used to explore the impact of these interventions on different aspects of psychosocial and existential distress. The qualitative feedback was analysed using content analysis to determine the themes and sub-themes of benefit derived from the bundled interventions. Results: Four major themes defined the dignity experience: physical concerns, psychological concerns and coping mechanisms, social concerns and spiritual concerns and coping mechanisms. These themes and the numerous sub-themes provide an understanding of the total dignity experience of South African patients living with advanced disease. This study provided quantitative and qualitative data illustrating the impact of Dignity Therapy and Guided imagery, which proved to enhance the dignity experience of patients with advanced disease. The beneficial impact of Dignity Therapy and Guided Imagery on the dignity experience of dying patients was documented with confirmations on measures of helpfulness (100%), satisfaction (100%), a heightened sense of dignity (75%), purpose (100%) and meaning in life (92%). Further endorsements were expressed in terms of 83% sharing that it had lessened their sense of suffering, and feelings of anxiety and depression (92%) and improved their will to live (83%). The participants also expressed that the beneficial impact of interventions would spread beyond themselves to help their families (92%) and to benefit their relationship with their healthcare providers (92%). The interventions were shown qualitatively to have a beneficial impact on the Physical, Psychological, Social and Spiritual Domains of the participants' lives and these emerged as the four themes with various sub-themes. Conclusion: With this awareness of the biopsychosocial and existential concerns and psycho-existential coping mechanisms that affect the total dignity experience, healthcare providers can optimise dignity conserving care to improve the quality of lives of patients living with advanced disease. In this small study, Dignity Therapy and Guided Imagery are shown to be relevant, feasible and acceptable, short psychotherapeutic interventions that can be conducted at the bedside by healthcare providers to enhance the dignity experience of patients. A Guided Imagery focused on intrinsic dignity is shown to be a novel beneficial 5-minute intervention that can augment Dignity Therapy, or be used on its own, to affirm and strengthen the experience of the intrinsic worth of patients with advanced disease. Healthcare professionals have an influence in the area of the extrinsic sources of dignity in advanced disease, and can enhance dignity in providing respectful compassionate care. To add to the knowledge on dignity research, this study specifically highlights the need to affirm intrinsic dignity in dying patients, to affirm their personal worth.